Efficacy and Safety of up to 2 Years of Treatment With TransCon hGH (Lonapegsomatropin) in Treatment-Naïve and Treatment-Experienced Children With Growth Hormone Deficiency - Maniatis, Aristides K (J Endocr Soc, 2021)
Background: Once-weekly TransCon hGH (lonapegsomatropin) is an investigational long-acting prodrug of somatropin in development for GHD. In the pivotal 52-week phase 3 heiGHt trial, lonapegsomatropin demonstrated superior annualized height velocity (AHV) compared to the same weekly dose of daily somatropin in treatment-naïve children with GHD. In the 26-week fliGHt trial, switch from daily somatropin to lonapegsomatropin provided continued growth and maintained a good safety profile. Methods: Results are reported from heiGHt and fliGHt subjects who continued into the open-label long-term extension enliGHten trial (data cut: June 1(st) 2020). Subjects received either lonapegsomatropin (Group A; vial/syringe) or daily somatropin (Group B; pen device) in heiGHt, or lonapegsomatropin in fliGHt (Group C; vial/syringe). Upon entry into enliGHten, all subjects received lonapegsomatropin via vial/syringe, with subsequent switch to TransCon hGH Auto-Injector when available. Average IGF-1 was obtained on post-dose Day 5 (±1) in enliGHten. A by-visit ANCOVA model was used for numeric efficacy endpoints. Results: A total of 298 (98%) subjects continued into enliGHten. (A: n=103; B: n=55; C: n=140). The treatment difference in LS mean ∆ height SDS (A vs B) at the end of heiGHt (Week 52, 1.10 vs 0.96, P=0.015) was sustained through Week 104 (1.61 vs 1.49, P=0.158). For Group C, height SDS improved from −1.42 at fliGHt baseline to −0.69 at Week 78. AHV was within the expected range for 2(nd) year therapy. Among children who switched (B), an attenuation in the expected 2(nd) year decline of AHV suggested that lonapegsomatropin had an improved treatment effect relative to the previous daily somatropin. Mean (SD) average IGF-1 SDS remained stable and generally within the expected range for all groups (Week 104, A: 0.95 [1.22], B: 1.04 [1.25]; Week 78, C:1.81 [1.08]). An improvement in injection site tolerability was observed after switching to the TransCon hGH Auto-Injector; subjects and parents also indicated overall ease-of-use of the device (assessed by the Device Usability Questionnaire). With continued lonapegsomatropin treatment, the AE profile remained consistent with what was observed in the parent trials, with no new safety signals. Throughout enliGHten and the parent trials, non-neutralizing low-titer anti-hGH binding antibodies were detected post-dose in a total of 15 subjects (5.0%). Lab parameters were stable and generally remained within the normal range throughout the trials. As of the data cut, 2 subjects have achieved near adult height (AHV <2 cm/year over the last 9 months or bone age >14 [females] or >16 [males]) and thus have completed the trial. Conclusions: Children treated with lonapegsomatropin showed continued improvement of height SDS through their 2nd year of therapy. Lonapegsomatropin continued to demonstrate a safety profile comparable to that of daily somatropin therapy.